Regular Exercise, Plasminogen Activator Inhibitor-1 (PAI-1) Activity and the 4G/5G Promoter Polymorphism in the PAI-1 Gene - Väisänen, Sari B.; Humphries, Steve E.; Luong, Le-Anh; Penttilä, Ilkka; Bouchard, Claude; Rauramaa, Rainer (Thrombosis and Haemostasis, 1999)
The aim of this controlled randomised clinical trial was to investigate the effects of regular low to moderate intensity physical activity on plasminogen activator inhibitor-1 (PAI-1) activity during three years while taking into account the 4G/5G polymorphism in the promoter of the PAI-1 gene. Male subjects (age 52-62 years, n = 132) were randomised into an exercise or a (non-intervention) reference group. Aerobic threshold increased by 8.8% (p = 0.025) in the exercise group, and decreased by 1.1% in the non-intervention group, while PAI-1 activity did not change significantly in either study group. However, homozygotes for the 4G allele in the exercise group showed a 36% reduction in PAI-1 (p = 0.025). In conclusion, although regular moderate physical activity did not decrease PAI-1 activity in the whole group, regular exercise may be effective for controlling elevated PAI-1 level in subjects homozygous for the 4G allele.
Keywords: Plasminogen activator inhibitor-1; DNA polymorphism; exercise training; randomised clinical trial; population based study